Characterization of montmorillonite surfaces after modification by organosilane - Kang Song; Giselle Sandí
X-ray powder diffraction (XRD), thermal gravimetric analysis (TGA), surface area measurements, and near-edge X-ray absorption fine structure (NEXAFS)spectroscopy were used to examine the surface properties of organosilane-modified smectite-type aluminosilicate clays. Organic modified clays derived from the reactions of montmorillonite (containing 93-95
Keywords: CLAY-ORGANIC INTERACTIONS; MONTMORILLONITE; ORGANIC COATING; SILANE; SURFACE MODIFICATION